Kontribusi Sport Massase Teknik Effleurage Dan Petrissage Terhadap Penurunan Lelah Pasca Latihan Pencak Silat Atlet Al Azhar Bengkulu: The Contribution of Sport Massage Effleurage and Petrissage Techniques to Reduction in Fatigue After Pencak Silat Training for Al Azhar Athletes Bengkulu - Lubis, Sulaeman; Pujianto, Dian; Prabowo, Andika (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Abstract  This study aims to determine the contribution of sport massage with effleurage and petrissage techniques to reducing post-exercise fatigue. This type of research is descriptive research. The research sample amounted to. The results of all research tests carried out before and after doing sport massage treatment with effleurage technique on reducing post-exercise fatigue, it can be concluded that: sport massage effleurage and petrissage techniques have a good contribution, obtained rtable of 0.361 because the correlation coefficient between rxy = 0.91 > 0.361 and the contribution of 91.80% and the test before and after doing the petrissage technique sport massage treatment to the reduction in post-exercise fatigue has a high contribution obtained rtable of 0.361 because the correlation coefficient between rxy = 0.95 > 0.361 and a contribution of 89.93% which means the contribution of the results before and after doing sport massage treatment with effleurage and petrissage techniques to decrease fatigue after training in Pencak Silat Athletes Al Azhar Bengkulu is significant and large. Keywords:  Effleurage, Petrissage, exercise decreased fatigue after